AN INVESTIGAITON INTO COHESIVE DEVICES USED IN HEALTH CARE ADVERTISEMNETS ON AMERICAN TELEVISION - Trương Văn Tuấn (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
Language of advertising is a very special communicative form in society with customers through given products or services in which language has its own characteristics that make it different from the other languages. Therefore, the thesis aims at analyzing healthcare advertisements on American television in terms of layout, cohesive devices. The descriptive method is employed to give detailed description of some typical features in healthcare television advertisements and the qualitative research approach was used for compiling the primary data of this thesis. The data for the theoretical study of this paper was gathered from linguistic books and the Internet. In addition, the study is based on a survey of 50 healthcare advertising video clips which were collected from American television channels. The findings show that healthcare television advertisements display a general layout with five parts: The Headline, the Body Copy, the Illustrations, the Signature Scenes and the Standing details. The grammatical cohesive devices such as reference, conjunctions, substitution and ellipsis as well as the lexical cohesive devices, reiteration and collocation are used with a large number in the healthcare television advertisements. It is hoped that the result of this study will really help viewers/customers understand the language of television advertising easily to make a right decision in choosing healthcare products/services. Especially, the result of the research is really useful for those who are interested in healthcare advertising on television and work for advertising agencies.